Do joint custody laws improve family well-being? - Martin Halla (IZA World of Labor, 2015)
Custody laws governing living arrangements for children following their parents' divorce have changed dramatically since the 1970s. Traditionally, one parent—usually the mother—was assigned sole custody of the child. Today, many divorced parents continue to share parental rights and responsibilities through joint custody arrangements. While joint custody laws have improved the situation of divorced fathers, recent empirical research has documented intended and unintended consequences of joint custody laws for families in such areas as family formation, labor force participation, suicide, domestic violence, and child outcomes.
Keywords: J12; J13; J18; K36; D13; 330; joint custody; marriage; divorce; fertility; suicide; child outcomes